The Short-Term Impact of Formal Controls on Subsequent Offending and Future Formal Controls in a German and UK City - Boers, Klaus (Journal of developmental and life-course criminology, 2023)
The study of sanctioning effects has a rich history in deterrence and labeling theory. Most analyses have only used official data to study these effects. Yet, some more recent studies indicate that it is necessary to investigate self-reported as well as official data since it appears that sanctioning has differential effects on self-reported delinquency and formal control interventions. The current study contributes to this small body of research by using propensity score matching to analyze panel data from an ongoing English (Peterborough Adolescent and Young Adult Developmental Study) and a German (Crime in the modern City) study. We estimated average treatment effects of system contacts on both reoffending and subsequent contacts for juveniles living in Peterborough (ENG) and Duisburg (GER). Our findings are that (1) although official contacts have no substantial effects on the prevalence or versatility of reoffending, (2) they substantially increase the risk of a future formal contact. These results were almost identical at both sites, which may indicate a more general finding on the effects of formal control interventions.